Seismic Performance of Reinforced Concrete Buildings in Thimphu, Bhutan - Thinley, K.; Hao, Hong; Tashi, C. (World Scientific Publishing Co. Pte. Ltd., 2016)
Inspite of its location in one of the most active seismic zones in the world, Bhutan has no seismic design code of its own and no detailed study on the performance of buildings under expected earthquake ground excitation has been carried out. In this study, probabilistic seismic hazard analysis is first carried out to predict the design ground motions in Thimphu, Bhutan for the return periods (RPs) of 475 and 2475 years. These ground motions are then used to assess the performance of three typical RC buildings in the capital city, Thimphu. Soil–structure interaction (SSI) is incorporated at different soil sites and the effects of SSI are discussed. Adequacy of using Indian Seismic Code in Bhutan is also studied and discussed. The study suggests that the typical buildings in Bhutan could undergo moderate to severe damages under the 475 year RP and could even collapse under the 2475 year RP ground motions. This study is the first such effort in predicting the design ground motions and then assessing the performance of the general building stocks in Bhutan. The result can guide the seismic preparedness of the country through proper design and mitigation measures.